2014
DOI: 10.5114/pjp.2014.43963
|View full text |Cite
|
Sign up to set email alerts
|

Parotid gland tumors in children – pre- and postoperative diagnostic difficulties

Abstract: Major salivary gland tumors are very rare in the developmental period. Confirming tumor changes in the salivary gland requires precise diagnostic imaging involving an ultrasonography scan, computed tomography and magnetic resonance. Needle aspiration biopsy (NAB) of the tumor is of high importance. Excision is the basic treatment method in cases of parotid gland tumor. The statistical data concerning tumors favor less invasive methods, which seems logical in the population of children. The surgical methods use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…However, a recent report suggested that computed tomography is not helpful for distinguishing benign and malignant disease but that magnetic resonance imaging features, such as T2 hypointensity, restricted diffusion, ill-defined borders, and focal necrosis, although not specific, should raise concerns about malignancy [15] . Occasionally, the use of fine-needle aspiration cytology or fine-needle core biopsy may be required to avoid major surgery in situations such a mass due to lymphoma [16,17] . The clinical utility of needle biopsy remains debatable, however, especially in younger patients, because of the need for an anaesthetic.…”
Section: Differential Diagnosis and Investigationmentioning
confidence: 99%
“…However, a recent report suggested that computed tomography is not helpful for distinguishing benign and malignant disease but that magnetic resonance imaging features, such as T2 hypointensity, restricted diffusion, ill-defined borders, and focal necrosis, although not specific, should raise concerns about malignancy [15] . Occasionally, the use of fine-needle aspiration cytology or fine-needle core biopsy may be required to avoid major surgery in situations such a mass due to lymphoma [16,17] . The clinical utility of needle biopsy remains debatable, however, especially in younger patients, because of the need for an anaesthetic.…”
Section: Differential Diagnosis and Investigationmentioning
confidence: 99%
“…Pediatric facial nerve paralysis has been also described associated to leukemia (in many cases bilateral) or to parotid gland tumors [9,18] . Finally, traumas such as temporal bone fractures (longitudinal, transverse and oblique) can cause facial nerve palsy in children [19] , while iatrogenic paralysis can occur after surgery of the parotid gland, middle ear or mastoid [8,9] .…”
Section: Epidemiology and Etiopathogenesismentioning
confidence: 99%
“…It is necessary to investigate about the onset and the time course of the paralysis and its eventual progression (e.g., a gradual onset, > 3 wk, may suggest a neoplastic etiology). All the associated symptoms should be identified, as well as any other comorbidities affecting the child [14,15,[18][19][20][21] . During the ENT examination, particular attention should be given to the inspection of the external auditory canal, the eardrum and the mastoid region.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…Tumors of the major salivary glands are very rare in juveniles, and 70% of the lesions occur between 16 and 20 years of age [1]. Although hemangiomas are diagnosed most frequently, the most common epithelial tumors of the major salivary glands in young patients are still pleomorphic adenomas [2].…”
Section: Introductionmentioning
confidence: 99%